Mental Health Status Of Healthcare Workers In Primary Health Clinics In Sepang - Stephen Tan Eyu Zhen; Madeehah T Mohd, Tengku Amatullah; Siti Munirah Mohamad Ismail; Gan Chai Woon; Tan Fang Chin; Ong Wee Meng; Sivaneswary A/P Kaliappan; Nurhidayah Abdul Manan; Nuha Arifah Abd Aziz; Aida Syarinaz Ahmad Adlan; Delima Kalsom Abdul Wahab; Farizah Mohd Hairi (Malaysian Psychiatric Association, 2024)
Indexed by MyCite